TINGKAT BAHAYA EROSI LAHAN REKLAMASI TAMBANG BATUBARA KECAMATAN TEBO ILIR KABUPATEN TEBO PROVINSI JAMBI - Hardian Wijaya; T. Listyani R.A; Rr. Amara Nugrahini (Institut Teknologi Nasional Yogyakarta, 2025)
In general, coal mining activities in Indonesia use open mining methods, which can cause several negative impacts on the environment due to changes in environmental conditions. Land clearing results in high rates of erosion and a decrease in soil quality. This research is aimed at determining the physical and chemical characteristics of the soil, the rate of erosion on mine reclamation land during different reclamation periods. The methods used in this research are literature study, taking soil samples in the field, analyzing erosion rates using the Universal Soil Loss Equation (USLE) method and to determine the physical and chemical quality of the soil through laboratory tests. The erosion rate value on reclaimed land A is 21.39 tons/ha/year, which is in erosion class II, light category. Reclamation land B 169.86 tonnes/ha/year with erosion class III, moderate category. The value of the erosion rate is greatly influenced by slope factors and vegetation factors which can improve the soil structure to make it more stable.